(untitled) (Third Sector Social Economic Review, 2024)
Innovation and productivity, which have a complex and two-way relationship, are two essential factors that ensure economic growth, competitiveness, and social progress. Innovation increases productivity by providing new technologies, processes, and products that reduce costs and simplify operations. Productivity triggered by technological developments can be achieved by innovation that requires resource saving and more investment in research and development. This study aims to reveal the main innovation and productivity ecosystem development trends by using different quantitative and qualitative parameters in the interdisciplinary research field. The study was designed as a bibliometric research to map the interaction between innovation and productivity comprehensively. This study covers 4884 documents related to innovation and efficiency published in the Web of Science (WoS) database between 1981 and 2023. Performance analysis and scientific mapping of the documents were conducted to reveal common themes, general trends, and key empirical findings in the field. Analysis results show that innovation and productivity should not be considered independent variables. While the focus of research in the field was research development and growth until the mid-2010s, after 2015, it has turned to the ability to understand the value of new knowledge, internalize it, and adapt it to purposes. Policymakers and business leaders should evaluate research findings as part of a harmonious strategy for economic development and sustainable growth.